Plasmonic Hot Spots on Topological Insulator Nanotips for Enhancing Light Interaction with MoS2 Atomic Monolayer [invited] - Yiqiao Zhang; Hua Lu; Zengji Yue; Mingwen Zhang; Xuetao Gan; Jianlin Zhao (Advanced Photonics Research)
Topological insulators (TIs) have unique topologically protected conducting surface and insulating bulk states, which provide a novel platform for plasmonic excitation and related nanoscale functional devices. Exploring plasmon‐enhanced interactions between light and atomic‐layered semiconductors in TI nanostructures is particularly significant for optoelectronic applications of TIs. Herein, the Sb2Te3 TI nanotips are fabricated by using focused ion beam lithography technique and the plasmonic hot spot behaviors are investigated on the TI nanotips. The numerical simulation shows that there exists a distinct reinforcement of light field on the Sb2Te3 TI nanotips, which stems from the TI‐based plasmonic hot spot effect. Moreover, the obvious enhancement of photoluminescence (PL) emission from a molybdenum disulfide (MoS2) monolayer integrated onto the Sb2Te3 TI nanotips is experimentally observed. The PL intensity of MoS2 layer on the Sb2Te3 nanotips can be effectively improved by about five‐fold due to the plasmonic hot spot‐induced field reinforcement when compared with that of MoS2 without the Sb2Te3 nanotips. These results will open a new avenue for optoelectronic applications of TIs, especially in nanoscale enhanced PL emission.